PELANGGARAN HUKUM TERHADAP PEMANFAATAN SEMPADAN SALURAN IRIGASI RENTANG KABUPATEN INDRAMAYU - Sakti, Sahne Fa Alhama Ibrahim (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Function changes part or all of the land area from the original function is problem about landuse, one of them is over the function on irrigation stream buffer. Stream buffer is boundary line in left and right trough irrigation set as due protection irrigation. Change area utilization on stream buffer irrigation in Indramayu district dominated by increase residential area that requires and special control is the area that has strategic value and on the regional management must priority. The results showed that there was a violation of Article 80 of PERDA of Indramayu No.22 of 2007 for the construction of buildings on the border of the irrigation because the utilization of the irrigation boundary is not appropriate as regulated in the regulation. Impacts of building construction on the irrigation border include a decrease in river water quality, increased scouring of river banks, and reduce the amount of aquatic life. Strategies to control and monitor space utilization are carried out through persuasive and repressive methods.